Binary Colloidal Nanoparticle Concentration Gradients in a Centrifugal Field at High Concentration - Xu, Xufeng; Franke, Tina; Schilling, Kristian; Sommerdijk, Nico A. J. M.; Cölfen, Helmut (My University, 2019)
Binary colloidal nanoparticles have been found to form different types of crystalline phases at varied radial positions in a centrifugal field by Chen et al (ACS nano 2015, 9, 6944-50). The variety of binary phase behaviors resulted from the two different nanoparticle concentration gradients but to date the gradients can only be empirically controlled. For the first time, we are able to measure, fit and simulate binary hard sphere colloidal nanoparticle concentration gradients at high particle concentration up to 30 vol%, which enables tailor-made gradients in a centrifugal field. By this means, a continuous range of binary particle concentration ratios can be accessed in one single experiment to obtain an extended phase diagram. By dispersing two differently sized silica nanoparticles labeled with two different fluorescence dyes in a refractive index matching solvent, we can use a Multi-Wavelength Analytical Ultracentrifuge (MWL-AUC) to measure the individual concentration gradient for each particle size in sedimentation-diffusion equilibrium. The influence of the remaining slight turbidity at high concentration can be corrected using the MWL spectra from the AUC data. We also show that the experimental concentration gradients can be fitted using a non-interacting non-ideal sedimentation model. By using these fitted parameters, we are able to simulate nanoparticle concentration gradients, which agreed with the subsequent experiments at a high concentration of 10 vol% and thus allowed for the simulation of binary concentration gradients of hard sphere nanoparticles in preparative ultracentrifuges (PUC). Finally we demonstrated that by simulating the concentration gradients in PUC, a continuous and extended binary nanoparticle phase diagram can be obtained by simply studying the structure evolution along the centrifugal field for one single sample instead of a large number of experiments with discrete compositions in conventional studies.
Keywords: Binary nanoparticle concentration gradients; binary nanoparticle phase diagram; high particle concentration; sedimentation−diffusion equilibrium; 540